Before I forget: From personal memory to family history - Lindley, Siân (Human Computer Interaction, 2012)
This paper presents findings from a field study of eight persons over the age of 50, who were undertaking a range of activities with the intention of ‘recording their memories for posterity’. We describe practices associated with dealing with inherited family archives; the creation of new artefacts, such as scrapbooks and collections of letters, out of repurposed archived materials; and the recording of one’s memoirs. Our analysis leads us to emphasise a distinction between ‘personal’ memory and memory ‘for family’, noting that while memory is used in the construction of a sense of one’s own history, and in enabling personal reflection on the past, the work that is bound up with processing archives and producing new artefacts is heavily influenced by a desire to make them accessible and relevant to children and grandchildren, both now and in the future. The tending to, and crafting of, these materials can be understood as a means of creating a ‘joint’ past and reinforcing a wider family narrative. We conclude that through these practices, memory was used a resource for self, but also for future family life.